Outcome and treatments of dogs with aortic thrombosis: 100 cases (1997‐2014). (15th August 2020) - Ruehl, Mackenzie; Lynch, Alex M.; O'Toole, Therese E.; Morris, Bari; Rush, John; Couto, C. Guillermo; Hmelo, Samantha; Sonnenshein, Stacey; Butler, Amy; Guillaumin, Julien
Abstract: Background: Aortic thrombosis (ATh) is an uncommon condition in dogs, with limited understanding of risks factors, outcomes, and treatments. Objectives/Hypothesis: To describe potential risk factors, outcome, and treatments in dogs with ATh. Animals: Client‐owned dogs with a diagnosis of ATh based on ultrasonographic or gross necropsy examination. Method: Multicentric retrospective study from 2 academic institutions. Results: One hundred dogs were identified. Anti‐thrombin diagnosis, 35/100 dogs were nonambulatory. The dogs were classified as acute (n = 27), chronic (n = 72), or unknown (n = 1). Fifty‐four dogs had at least one comorbidity thought to predispose to ATh, and 23 others had multiple comorbidities. The remaining 23 dogs with no obvious comorbidities were classified as cryptogenic. Concurrent illnesses potentially related to the development of ATh included protein‐losing nephropathy (PLN) (n = 32), neoplasia (n = 22), exogenous corticosteroid administration (n = 16), endocrine disease (n = 13), and infection (n = 9). Dogs with PLN had lower antithrombin activity than those without PLN (64% and 82%, respectively) ( P = .04). Sixty‐five dogs were hospitalized with 41 subsequently discharged. Sixteen were treated as outpatient and 19 euthanized at admission. In‐hospital treatments varied, but included thrombolytics (n = 12), alone or in combination with thrombectomy (n = 9). Fifty‐seven dogs survived to discharge. Sixteen were alive at 180 days. Using regression analysis, ambulation status at the time of presentation was significantly correlated with survival‐to‐discharge ( P  < .001). Conclusions/Clinical Importance: Dogs with ATh have a poor prognosis, with nonambulatory dogs at the time of presentation having worse outcome. Although the presence of comorbid conditions associated with hypercoagulability is common, an underlying cause for ATh was not always identified.